Reading poems: an intercultural comparative analysis - Chang, Zong Lin (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2003)
With the feedback from the subjects being presented and discussed, this article aims to explain how different readers in English and Chinese cultures read, engage with and interpret poems and how they respond to the culturally loaded texts by writers from same cultural background and from different cultural backgrounds. The study of the data seeks to illustrate how the subjects are influenced by their 'acculturation' (Kramsch, 1998a, p. 125) and education. It attempts to exemplify how the subjects read and respond in their communications in terms of their different schemata which result in the differences and similarities in their interpretations and responses when they read poems and the culturally loaded discourses. It aims to present different ways in which these subjects form and utilize images and how they interpret metaphors in their reading process. As a supplementary part of the research, there is also discussion on both the advantages and the disadvantages of the research methods used for such a study.